Malignant adnexal tumors: a rare case of cutaneous malignancy - Venugopal, Shwetha; Madhu, C. P.; B., Akshata Kamath (International Surgery Journal, 2017)
Skin adnexal tumours (SAT) are a large and diverse group of benign and malignant neoplasms, which exhibit morphological differentiation towards one of the different types of adnexal epithelium present in normal skin: pilosebaceous unit, eccrine and apocrine. In present case, a forty-five-year-old female patient presented to us with a solitary erythematous swelling over the left chest wall since two years, which was approximately 3 × 3 cm in size, slowly growing to its present size of 10X5 cm, painless, hard in consistency with smooth erythematous surface, non-mobile and not associated with discharge or axillary lymphadenopathy.